Niceness or toughness? Gendered norms as regulators of employee communication of risks and problems - Kristina Hermansson; Erica Nordlander; Lotta Dellve (Social Sciences and Humanities Open)
Various forms of silence counteract the idea of an open organisation. A work environment in which employees express themselves freely about risks and problems, is a prerequisite for a sustainable and safe working environment. Diverse types of risks and problems must be detected, discussed and when relevant reported and subsequently managed. In relation to other factors, gender-stereotypical norms influence safety and health management, and affect communication regarding risks and injuries. By using focus groups and individual interviews, this study aims to investigate how employees' silence and communication about risks and problems in the workplace relate to gender norms, focusing municipal organisations in Sweden. The theoretical starting point is a critical gender perspective, focusing employee communication and silence. The research questions are: (i) What gendered norms can be found in employees' communication regarding risks and problems at work? (ii) How are these norms being manifested verbally? (iii) In what ways may these norms affect employee communication including silence? Analyses of clusters of gendered norms influencing employees’ communication about risks and problems at their workplace identified two themes: norms of toughness and norms of niceness. Both of them may pave the way for a workplace culture, where employees withhold information to avoid negative consequences; hence striving to maintain their position in the group rather than contributing to a safer, better-functioning working environment for everyone.